Analisis Dinamis Pengaruh Suku Bunga The Fed, Nilai Tukar Dollar AS dan Harga Minyak Terhadap Harga Emas Di Indonesia - Elviera Putri Amarta; Any Widayatsari; Darmayuda Darmayuda (LPPM Universitas Sains dan Teknologi Komputer, 2026)
The aim of this study is to analyze the long-term and short-term effects of the Federal Reserve (The Fed) interest rate, the US dollar exchange rate, and crude oil prices on gold prices in Indonesia. This study uses the Federal Reserve (The Fed) interest rate, the US dollar exchange rate, and the West Texas Intermediate (WTI) crude oil prices as independent variables, with the dependent variable being the price of gold in Indonesia. The data used in this study is secondary data in the form of montly time series data obtained during the period from Januari 2009 to December 2024. The analysis method used in this study is Autoregressive Distributed Lag (ARDL), which was chosen because i tis capable of estimating short-term and long-term relationship and can be used on variables with different levels of stationarity. The results of the study indicate that in the long term, the Federal Reserve interest rate affects the price of gold in Indonesia. Meanwhile, in the short term, the Federal Reserve interest rate, the exchange rate the US dollar, and oil prices do not affect gold prices in Indonesia.